The Impact of Product Quality, Brand Image and Service Quality toward Customer Loyalty - Fitrajaya, Prawira Hadi; Nurmahdi, Adi (International Humanities and Applied Science Journal, 2019)
This study aims to examine the effect of product quality, brand image and service quality toward customer loyalty at Starbucks. The research data was taken from a survey conducted on customers of Starbucks with the criteria have been purchased a minimum of 12 times a month. The research method used is linear regression with 3 independent variables processed using the SPSS Statistics program. The results of the research stated that the coefficient of determination is 0.494, which means the percentage contribution of independent variables (product quality, brand image, service quality) to the dependent variable (service loyalty) is 49.4%. The remaining 50.6% is influenced or explained by other variables not included in this research model. The results showed that partially, the Product Quality variable had a significantly positive effect on customer loyalty while the Brand Image and Service Quality variables had no effect on Customer Loyalty. However, simultaneously there is a significant effect of Product Quality, Brand Image and Service Quality on Starbucks Customer Loyalty.